A informação contábil explica o risco de crédito? - Gallina, André Sekunda (2021)
This thesis aims to analyze the relationship between aggregate accounting information and credit risk. Accounting information, as discussed in the literature, has several useful properties, contributing to the understanding of price behavior in the stock market, the estimation of future cash flows and company profits or the analysis of individual risk of companies and sectors economical. Furthermore, because accounting information carries elements of the real economy, it is also useful to understand and predict macroeconomic variables such as GDP, inflation, unemployment and others. However, there are few studies that aim to analyze the relationship between accounting information and credit risk at the macroeconomic level). In turn, the Financial Fragility Hypothesis (HFF) constitutes a current of research in Economie Sciences that analyzes the risk of an economy from the characteristics of the debt of economic agents, making it possible, therefore, to measure the level of financial fragility through accounting information. Although financial fragility can be evidenced by firms accounting information, research analyzing the relationship between financial fragility and credit risk was not found in the current literature. Aiming to fill this gap, this research proposes to investigate the relationship between accounting information and credit risk in light of the informativeness of accounting information and the HFF. Based on this theoretical support, two hypotheses are formulated for the research: Hypothesis 1 (First article) - The aggregate financial fragility of firms, estimated based on the accounting information of the debt structure, explains the credit risk, and Hypothesis 2 (Second article) - The aggregated accounting information of firms is useful to explain sovereign credit risk at the country level. To test them, the thesis starts from a quantitative approach, using vector autoregressive models (VAR), performing impulse response analysis and variance decomposition. The sample is composed of G-7 and BRICS companies with data from 2001 to 2019 (excluding the year 2020 due to the COVID-19 pandemic). As main findings, it was found that, with regard to the analysis of financial fragility of firms estimated from accounting information, this measure is useful to explain the behavior of sovereign credit risk, both in the sample of developed countries and in the developing countries, although with reduced levels of explanatory power when analyzing the decomposition of the credit risk error variance by financial fragility. As for the direct analysis of accounting information and credit risk, evidence is in the sense that shocks in accounting information result in significant responses to credit risk, an expected result consistent with accounting theory (Ball & Brown, 1968). However, the signal verified in the response to the shock does not always behave as expected, especially in the sectorial analysis. Thus, the two research hypotheses are supported by empirical evidence. The findings are potentially useful for the market, especially the investment industry, because using the risk analysis proposed in the thesis, and considering that accounting information is a reliable source of information, decisions can be taken more quickly and less onerous in terms of capital allocation, and for policymakers and governments in general, as they can contribute to better planning and execution of macroeconomic policies. In addition, the results can be useful to policymakers and governments in general, as they can contribute to better planning and execution of macroeconomic policies using accounting information.